System development for ethics in digital record archive: insight from strategically critical review - Othman, Muhammad Atiullah; Raja Hassan, Tuan Rusmawati; Suliman, Mohd Saipuddin; Huda, Miftachul (Springer Nature, 2026)
The important impact of technological progress provided in society has consistently emerged in the education sector. The truth is that an electronic based archival arrangement has been the transitional route for delivering resources, materials, and data for educational purposes. This paper intends to explore the real implementation about the electronic based archival arrangement utilized to support the users’ instructional process mainly in education context. The additional detail is to examine closely about the global demands in improving such practical-based initiative regarding the advancement of learning technology to achieve effectiveness. A critical evaluation of recent literature, encompassing referenced articles relevant into the topic being discussed has been performed. The result of this study indicated that strategic efforts aimed at comprehending the system development for an electronic archive design notably recommended for improving both the process and efficiency in reaching the learning objectives. The central focus attempts in providing the valuable point to enhancing the processes, procedures and pathways that support technology-driven digital learning in the educational sector.